United States : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
The slow-paced growth rate of the U.S. economy, notwithstanding the bolstering attempts is disheartening. Implementing financial reforms and highly accommodative monetary policy are hoped to have a desired effect. Deficit reduction, debt ratio stabilizing strategies, removal of fiscal cliff uncertainties, effective implementation of housing, and labor market holstering policies need immediate attention in the Executive Board's view. Underscoring the effect on global economy growth and stability, Directors commended U.S. efforts in fostering international coordination on financial regulatory reforms and in securing successful multilateral trade negotiations.